2012
DOI: 10.5539/jas.v5n1p130
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Efficiency in Clones of Conilon Coffee for Phosphorus

Abstract: The objective of this study was to evaluate the nutritional efficiency of phosphorus in clones of conilon coffee, in greenhouse condition. A factorial design 13 x 4 was used, with three replications, and the factors being: 13 clones that compose the clonal cultivar "Vitória Incaper 8142" and four levels of phosphorus fertilization (0%, 50%, 100% and 150% of the recommended P 2 O 5 for the culture) in a completely randomized design (CRD). The cultivation consisted of a period of 150 days, then in each experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 15 publications
1
18
0
4
Order By: Relevance
“…The nutritional content in plant tissues; the efficiency in which the plants acquire, translocate and utilize the nutrients; and tolerance to cultivation in environment with low fertility have all been successfully used as parameters to study the variability among genotypes of C. canephora and to identify groups with different traits (Martins et al, 2013a;2013b;Colodetti et al, 2014;Machado et al, 2016;Martins et al, 2015b;Starling et al, 2018). Differences among genotypes were observed for the content of all macronutrients in green tissues, and the magnitude of the genetic parameters showed that nutritional contents can be greatly influenced by the genetic constitution (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional content in plant tissues; the efficiency in which the plants acquire, translocate and utilize the nutrients; and tolerance to cultivation in environment with low fertility have all been successfully used as parameters to study the variability among genotypes of C. canephora and to identify groups with different traits (Martins et al, 2013a;2013b;Colodetti et al, 2014;Machado et al, 2016;Martins et al, 2015b;Starling et al, 2018). Differences among genotypes were observed for the content of all macronutrients in green tissues, and the magnitude of the genetic parameters showed that nutritional contents can be greatly influenced by the genetic constitution (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…For many agronomic traits, the existence of high genetic diversity had been reported, e. g., Colodetti et al (2014) and Martins et al (2013c), studying improved genotypes of C. canephora in environments with different levels of nutritional stresses, reported the expression of different growth behaviors and nutritional efficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have classified genotype 24 as nutritionally efficient, but unresponsive to increases in P fertilization, and genotype 32 as inefficient, but responsive to phosphorous fertilization. This may partially explain the fact that tolerance is related to the capacity of the genotypes to express efficiency in environments with nutritional limitations, and indicates that genotypes classified as intolerant may be, in most cases, very responsive to increases in P fertilization to recommended levels (Martins et al, 2013a). This direct relationship was evidenced for the genotypes in this study (Table 4), except for genotypes 73 and 153, which have been previously classified as inefficient and unresponsive (Martins et al, 2013a), and both were identified here as intolerant.…”
Section: Differential Tolerance To An Environment With Restricted Phomentioning
confidence: 99%
“…In contrast, some studies have reported that genotypes of Conilon coffee with early maturation (genotypes 02, 31, and 153) have higher growth rates and accumulation of nitrogen (N), P, potassium, calcium, magnesium, sulfur, and dry matter (Morais et al, 2012;Prezotti and Bragança, 2013;Partelli et al, 2013Partelli et al, , 2014. However, other studies showed that, in recommended growing conditions, early maturation may be linked to the efficiencies of absorption and utilization of P, and when modifying the supply of P, the behavior of genotypes varies (Martins et al, 2013a, Martins et al, 2013c, with no apparent evidence of change in the levels of tolerance.…”
Section: Relationship Between Tolerance and Ripening Cyclementioning
confidence: 99%